American history : the modern era since 1865 - Ritchie, Donald A. (Glencoe/McGraw-Hill, 1999)
Creating a Nation prehistory to 1815; Forging a Nation 1815-1877; New Horizons 1860-1900; Entering a New Century 1867-1920; Crusade and Disillusion 1914-1932; Times of crisis 1932-1960; Redefining America 1954-Present.